1999
DOI: 10.1128/aem.65.11.5177-5181.1999
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Shiga Toxin-Producing Escherichia coli O26, O111, and O157 in Bovine Feces

Abstract: Cattle are an important reservoir of Shiga toxin-producingEscherichia coli (STEC) O26, O111, and O157. The fate of these pathogens in bovine feces at 5, 15, and 25°C was examined. The feces of a cow naturally infected with STEC O26:H11 and two STEC-free cows were studied. STEC O26, O111, and O157 were inoculated into bovine feces at 101, 103, and 105 CFU/g. All three pathogens survived at 5 and 25°C for 1 to 4 weeks and at 15°C for 1 to 8 weeks when inoculated at the low concentration. On samples inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(54 citation statements)
references
References 18 publications
1
50
2
1
Order By: Relevance
“…The PFGE data analysis revealed that various STEC clonal types, such as C4 (serotype O113:NM) or C5 (serotype O91:H10), were able to persist for at least 2 months in cowpats. The survival times of STEC in this natural context did not significantly differ from those previously reported under controlled experimental conditions, for which E. coli O157:H7 was found to survive from 49 to 126 days in bovine faeces, and STEC O26:H11 and O111 persisted for 112 and 70 days in feces held at 15°C, respectively (Fukushima et al 1999;Duffy 2003). Overall, these finding supports the fact that cowpats could provide an effective protective medium to STEC as previously described for total coliforms (Bohn and Buckhouse 1985) and may constitute an important and persistent source for further environmental contamination with STEC.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The PFGE data analysis revealed that various STEC clonal types, such as C4 (serotype O113:NM) or C5 (serotype O91:H10), were able to persist for at least 2 months in cowpats. The survival times of STEC in this natural context did not significantly differ from those previously reported under controlled experimental conditions, for which E. coli O157:H7 was found to survive from 49 to 126 days in bovine faeces, and STEC O26:H11 and O111 persisted for 112 and 70 days in feces held at 15°C, respectively (Fukushima et al 1999;Duffy 2003). Overall, these finding supports the fact that cowpats could provide an effective protective medium to STEC as previously described for total coliforms (Bohn and Buckhouse 1985) and may constitute an important and persistent source for further environmental contamination with STEC.…”
Section: Discussioncontrasting
confidence: 48%
“…The long-term persistence of STEC in faeces and soil has been extensively documented. According to the experiments, the survival of STEC in bovine faeces ranged from 49 to 126 days and from 25 to more than 365 days in faeces-amended soil (Bolton et al 1999;Fukushima et al 1999;Fenlon et al 2000;Jiang et al 2002;Duffy 2003;Nicholson et al 2005;Fremaux et al 2008). However, most of the experiments were performed in laboratory or in experimental areas limitedly exposed to outside environmental conditions, and ⁄ or using either soil or faecal samples experimentally inoculated with STEC strains, which can affect results.…”
Section: Introductionmentioning
confidence: 99%
“…As the prevalence of cattle carrying STEC in their faeces may be high, 6% reported in a US study (Cray et al 1996) to 71% in a French study (Pradel et al 2000), and as STEC is known to survive for long periods in cow faeces (126 days at 15°C) (Fukushima et al 1999), manure that is a mix of animal excreta (faeces plus urine) and bedding could constitute an important vehicle for environmental STEC contamination (Pell 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous contamination of the environment with bovine fecal bacteria could have served as a source of infection for the diarrheic animal. It is documented that some serotypes of STEC, such as O157:H7, O26:H11, and O111:H Ϫ , can survive in bovine feces for a long time, especially at 15°C (12). However, we cannot discount the existence of a resident population of serologically diverse STEC strains in guanacos, including serotypes such as O26:H11, which could be responsible for the LPS O26 antibodies detected in the animals when they arrived at the Experimental Station.…”
mentioning
confidence: 88%